Belajar Sebagai Kehendak Manusia (Masyiatul I'bad) dalam Mendapatkan Ilmu Pengetahuan - Taofik Andi Rachman; Nuwadjah Ahmad; Andewi Suhartini (Universitas Muhammadiyah Prof Dr Hamka, 2021)
The human will to choose is a gift that Allah has given to them. Since early life, humans have the potential to choose certain attitudes in life. With this will of choice, human can be in goodness and also man can fall into sin. The factors that can influence this will are human reason and revelation sent down by Allah Almighty. The relevance of the human will to gain knowledge is to study hard to master the knowledge that humans need. This paper is compiled from a literature study that contains the human will and theological reviews of the human will in obtaining knowledge. The data is compiled, analyzed, and concluded so as to get an overview of the views of Islamic theology in gaining knowledge. The results of the study show that knowledge is essentially a sustenance from Allah swt. As Allah's sustenance, humans are required by Sharia to earn it seriously. Studying diligently is a human effort to master knowledge. This human will is an important matter for humans in obtaining and developing knowledge.